2003
DOI: 10.3171/spi.2003.99.3.0251
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to long-term outcome after decompressive surgery for ossification of the ligamentum flavum of the thoracic spine

Abstract: Object. Factors related to long-term surgical outcome of thoracic myelopathy caused by ossification of the ligamentum flavum (OLF) have not been fully investigated. To evaluate these factors, the authors reviewed medical records obtained in patients who had undergone decompressive surgery for thoracic OLF. Methods. Thirty-four patients in whom decompressive surgery was performed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
143
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(152 citation statements)
references
References 24 publications
4
143
5
Order By: Relevance
“…Early diagnosis and treatment are important for the postoperative functional prognosis. It is reported that the persistence of residual spasticity at follow-up may be due to irreversible changes within the cord that is caused by the significant cord compression and the delay between the onset of initial symptoms and surgical decompression [2,9,12,14]. In our series, the symptom duration was not related to the surgical outcome statistically, but, especially the short symptom duration, less than 6 months, was a relatively favorable factor to the surgical outcome.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Early diagnosis and treatment are important for the postoperative functional prognosis. It is reported that the persistence of residual spasticity at follow-up may be due to irreversible changes within the cord that is caused by the significant cord compression and the delay between the onset of initial symptoms and surgical decompression [2,9,12,14]. In our series, the symptom duration was not related to the surgical outcome statistically, but, especially the short symptom duration, less than 6 months, was a relatively favorable factor to the surgical outcome.…”
Section: Discussionmentioning
confidence: 44%
“…In our series, the symptom duration was not related to the surgical outcome statistically, but, especially the short symptom duration, less than 6 months, was a relatively favorable factor to the surgical outcome. Miyakoshi et al [9] classified the thoracic OLF into five types according to the range and morphological features of the ossification depicted on the preoperative CT scans at the narrowest spinal level: lateral, extended, enlarged, fused, and tuberous. They reported that there were no correlations observed between the types of OLF and preoperative neurological status or postoperative prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported Clinical characteristics and surgical outcome of TM caused by OLF Z Li et al that the location of OLF is less vulnerable in mobile segments such as the cervical and lumbar vertebra than in the thoracic vertebrae. 26,30,40,55,56 This phenomenon gives us insight about the pathogenetic mechanism of OLF. On the basis of the literature review, we hypothesized that biomechanical and anatomical factors might have a key role in thoracic OLF progression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lamina treated with laminoplasty may return to the preoperative position, the surgical procedure is relatively complicated and the long-term effect is less reliable than that of the surgical technique reported here. 56,65 As we all know, each surgical procedure has its own complications. Dural tears and CSF leakage are the most common complications of thoracic OLF surgery and can lead to CSF pseudocyst, respiratory obstruction, wound dehiscence and meningitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation